Evaluation of Fifteen Tomato Germplasm For Salt Tolerance - Nasrin, S; Mannan, MA; Islam, MM; Khan, SAKU; Rahman, SMM (Bangladesh Agronomy Journal, 2022)
Soil salinity is a serious threat to crop productivity which influence growth and productivity of crop plants. Salt tolerance differ species to species and variety to variety. Therefore, this research work was initiated to investigate the influence of salinity levels on growth and yield of tomato genotypes and to select suitable variety for salt affected areas. A two factor poly house experiment was conducted in completely randomized design in Khulna University, Bangladesh, during November 2019 to March 2020. Factor one was consisted of fifteen tomato varieties including eight improved varieties developed by Bangladesh Agricultural Research Institute (BARI) and seven cultivars collected from farmer’s field of Khulna region. Other factor was consisted of five levels of soil salinity viz. control, 4, 8, 12 and 16 dSm−1. Tomato genotypes and salinity usages both significantly dissimilar for the agro- morphogenic traits. The plant height, leaf traits and yield traits are negatively influenced by salinity level. The local variety Guli gave the highest plant height for all the treatments. Tomato var. BARI tomato-15 produced the maximum fruit weight plant-1 at control followed by 4dSm-1 and 8 dSm-1. Therefore, tomato var. BARI tomato-15 may be suitable for cultivation in the areas containing salinity up to 8 dSm-1. This may also help to further improve tomato cultivars in saline areas. Bangladesh Agron. J. 2021, 24(2): 43-54